Ethanolic Extract of Bark from Salix aegyptiaca Ameliorates 1, 2-dimethylhydrazine-induced Colon Carcinogenesis in Mice by Reducing Oxidative Stress. (2nd April 2016) - Bounaama, Abdelkader; Enayat, Shabnam; Ceyhan, Muserref Seyma; Moulahoum, Hichem; Djerdjouri, Bahia; Banerjee, Sreeparna
ABSTRACT: We have previously shown that ethanolic extract from bark (EEB) of Salix aegyptiaca (Musk Willow) can inhibit proliferation and motility and induce apoptosis in colon cancer cells. Tandem mass spectrometry revealed EEB to be rich in catechin, catechol, and salicin. The present study investigated the chemopreventive effect of HPLC-fingerprinted EEB on 1, 2-dimethylhydrazine (DMH)-induced aberrant crypt foci (ACF) formation in mice. DMH (20 mg/kg body weight) was weekly injected subcutaneously to mice for the first 2 weeks. EEB (100 and 400 mg/kg body weight) was provided orally from the 7th to 14th week, after which colon tissues were evaluated histologically and biochemically. DMH treatment induced high number of ACF; EEB significantly reduced the number and multiplicity of ACF, along with a restoration in goblet cells and mucin accumulation. EEB supplementation improved the markers of inflammation (myeloperoxidase and neutrophil infiltration) and oxidative stress. More importantly, EEB amplified apoptosis of neoplastic cells in the colon mucosa of DMH-treated mice. It also lowered levels of markers for early transformation events such as EGFR, nuclear β-catenin, and COX-2 in colon cancer cell lines HT-29 and HCT-116. The innocuity of EEB (up to 1600 mg/kg) to mice reinforces its potential as a chemopreventive agent.